An introduction to media scheduling - approaches and problems - Newall, John (Cranfield University, 1973)
This paper aims to provide an introduction to the various approaches which have been used in handling the problem of scheduling communication messages in competing media forms. The references included in the discussion are by no means exhaustive of the number of examples of applications of the different approaches. Instead, attention has been restricted to those studies which, either illustrate the basic principles of the individual appraoch, or suggest ways of overcoming the accompanying limitations. A number of major conceptual or methodological difficulties associated with the media problem are felt to be suffucuently important to warrant individual consideration. accordingly, seperate sections are devoted to the problems of speifying the objective function, weighting factors and the time element within media scheduling.